Biomimetic biphasic scaffolds for osteochondral defect repair - Li, Xuezhou (Regen Biomater, 2015)
The osteochondral defects caused by vigorous trauma or physical disease are difficult to be managed. Tissue engineering provides a possible option to regenerate the damaged osteochondral tissues. For osteochondral reconstruction, one intact scaffold should be considered to support the regeneration of both cartilage and subchondral bone. Therefore, the biphasic scaffolds with the mimic structures of osteochondral tissues have been developed to close this chasm. A variety of biomimetic bilayer scaffolds fabricated from natural or synthetic polymers, or the ones loading with growth factors, cells, or both of them make great progresses in osteochondral defect repair. In this review, the preparation and in vitro and/or in vivo verification of bioinspired biphasic scaffolds are summarized and discussed, as well as the prospect is predicted.